1988
DOI: 10.3406/jso.1988.2842
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Warlpiri women's personal names

Abstract: This article looks at Aboriginal personal names, an area of study neglected for over 40 years, and concentrate on an Aboriginal group in Central Australia. Personal names are considered to be linked to the Dreamtime, and the methods by which names are acquired, and the people involved in bestowing names, are discussed. It is argued that naming may be seen as a rite de passage. Usage of personal names, and the factors affecting such usage, are presented, along with some observations on the relationship of perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Personal names may have adaptive value due to, for example, their crucial role in human interactions (Dussart, 1988;Seeman, 1983). Liking for one's name may suggest better psychological well-being and, therefore, more psychological resources to cope with life difficulties (Gebauer et al, 2008;Joubert, 1990;Taylor & Brown, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal names may have adaptive value due to, for example, their crucial role in human interactions (Dussart, 1988;Seeman, 1983). Liking for one's name may suggest better psychological well-being and, therefore, more psychological resources to cope with life difficulties (Gebauer et al, 2008;Joubert, 1990;Taylor & Brown, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Name could represent ''a rite de passage'', a mark of cultural tradition, or a sign of religious faith (Dussart, 1988;Seeman, 1983). More important, a person's name usually functions as a unique social symbol representing the individual's identity (Dion, 1983).…”
Section: Introductionmentioning
confidence: 99%
“… 2. Dussart lived and conducted ethnographic fieldwork in Yuendumu in the early 1980s (see Dussart, 1988, 2000) and has continued to participate in Warlpiri women’s yawulyu during visits to this community over the subsequent decades. Curran lived in Yuendumu in the mid 2000s, where she undertook a song documentation project, and has continued to attend yawulyu ceremonial events, including as part of several other research projects (see Curran, 2020b; Gallagher et al, 2014; Warlpiri Women from Yuendumu, 2017).…”
mentioning
confidence: 99%
“…In four separate studies that were conducted over a twenty-year period, researchers found decided tendencies toward psychosis and neurosis among people with unusual and uncommon first names (Hartman, 1968) (Ellis, 1954) (Savage & Wells, 1948). Name could represent a mark of cultural tradition, or a sign of religious faith (Dussart, 1998). More important, a person's name works as a unique social symbol representing an individual's identity (Dion, 1983).…”
Section: Unusual Vs Common Namesmentioning
confidence: 99%